PENAMBAHAN LIMBAH BEKAS UNTUK PENINGKATAN KREATIVITAS DAN INOVASI PERALATAN MUSIK PADA MATA KULIAH ANSAMBEL MUSIK DI PRODI PENDIDIKAN SENI MUSIK JURUSAN SENDRATASIK FAKULTAS BAHASA DAN SENI UNIVERSITAS NEGERI SEMARANG (Universitas Negeri Semarang, 2018)
ABSTACT The state of the Ansembel subject stagnated equipment, in theory and standard of school music ensembles consisting of musical instrument recorders, piano and guitar accompaniment, in the ensemble further added violin melodies to this standard of school music, this was felt to be too monotonous, rigid, less attractive. On the basis that learning resources can be taken from anywhere. Then there needs to be creativity and innovation in terms of equipment, adding used goods as additional equipment with the aim of learning Music instruments are more interesting and quality. The method used is descriptive qualitative data collection observation, interviews and documentation, in the analysis of qualitative data added with research and development, because they have to test, modify equipment. The results showed that the use of used goods around was able to enhance learning creativity, especially in the addition of musical equipment in music ensemble courses, the equipment included bamboo sticks, drum pans, plastic barrels as bass drums, aqua bottles with seeds as Cabasa, while the innovation of musical ensemble equipment is in the form of adding angklung instruments and varied with Ansambel musical instruments that have been there before the results of this combination of equipment can certainly improve the learning outcomes of music ensembles Keywords: Utilization of used goods, Music ensemble.